PELATIHAN MICROSOFT EXCEL UNTUK REMAJA DI DESA SEGARA MAKMUR - Dwi Haryanto; Fida Fathiyah Addini (LPPM Universitas Abdurrab, 2023)
The community needs to acquire basic knowledge of how to use computers and laptops, especially considering Industrial Age 4.0. Microsoft Excel is computer software that can be used in many areas, especially in data processing. One way to learn Microsoft Excel is through lessons at junior high or high school level. However, this learning has not been evenly distributed, because there are residents who do not continue their education to the junior or senior high school level, the lack of teaching staff in the field of computers or the limited infrastructure of school computers. This is very unfortunate as Microsoft Excel is one of the most needed software in various industries, whether it's processing large amounts of data or doing simple administrative tasks. Understanding Microsoft Excel is important for society and should be learned from a young age, so that the learning process can run faster. The purpose of this service is to teach how to use Microsoft Excel software to young people aged 12 to 18 in Segara Makmur Village, Bekasi District. These young people have different skills and knowledge, so the training materials are divided into two levels. Although the basic Microsoft Excel formulas and operations taught at both material levels are similar, the examples of calculations and applications taught are different. The outcome of this activity is that a 12–18-year-old will be able to u.nderstand basic formulas in Microsoft Excel and apply them to school-level mathematics and statistical calculations. This ability becomes the initial provision for the young people to understand the use of Microsoft Excel